Slow church : cultivating community in the patient way of Jesus - Smith, C. Christopher; Wilson-Hartgrove, Jonathan, 1980- (Downers Grove, Illinois : IVP Books, 2014)
Fast food. Fast cars. Fast and furious. Fast forward. Fast ... church? The church is often idealized (or demonized) as the last bastion of a bygone era, dragging our feet as we're pulled into new moralities and new spiritualities. We guard our doctrine and our piety with great vigilance. But we often fail to notice how quickly we're capitulating, in the structures and practices of our churches, to a culture of unreflective speed, dehumanizing efficiency and dis-integrating isolationism. In the beginning, the church ate together, traveled together and shared in all facets of life. Centered as they were on Jesus, these seemingly mundane activities took on their own significance in the mission of God. In Slow Church, Chris Smith and John Pattison invite us to leave franchise faith behind and enter into the ecology, economy and ethics of the kingdom of God, where people know each other well and love one another as Christ loved the church.
A theological vision for slow church -- Terroir : taste and see -- Stability : fidelity to people and place -- Patience : entering into the suffering of others -- Wholeness : the reconciliation of all things -- Work : cooperating with God's reconciling mission -- Sabbath : the rhythm of reconciliation -- Abundance : the economy of creation -- Gratitude : receiving the good gifts of God -- Hospitality : generously sharing God's abundance -- Dinner table conversation as a way of being church.
Includes bibliographical references (pages 231-234).
Keywords: Communities -- Religious aspects -- Christianity; Church